Analisis Penyalahgunaan Data Pribadi Pelanggan dalam Perspektif Routine Activity Theory di Internet Service Provider X - Suwondo, Az Zahra Fitria; Nurhadiyanto, Lucky (VISA: Journal of Vision and Ideas, 2025)
This research aims to determine and analyze personal data protection regulations as a form of privacy rights in Indonesia and companies that use personal data for administrative purposes of a purchase of a company's services or products as well as to provide information to readers to anticipate the spread of personal data and remind that personal data is a privacy right of a person to be protected from cybercrime and reputation damage. The research method used in this research is qualitative research method. The data collection technique used was to conduct direct interviews with sources and secondary data from various journals related to data abuse, articles from government websites, and articles from other official websites. The subjects of the research are the sources who work in one office, namely the sales and supervisory area. The objective of the investigation is the regulation on the security of personal data of customers of company X. The motivation of the perpetrators is to seek personal gain, the target of the right perpetrator is the old customer, and the lack of effective supervision is an important factor in the occurrence of customer data brokers. The area of supervisor as the closest guardian must tighten the supervision and ensure SOPs are observed to prevent data abuse. Company X needs to focus on improving service quality, effective employee management, and strict supervision of customer personal data protection. Protecting personal data is not only about preventing financial or legal losses, but also about respecting and protecting individual rights, ining security, social well-being, and building confidence in business and social interactions.